Understanding and reducing delayed dental care for early childhood caries: a structural equation model approach - Mengmeng Wang; Yu Zhang; Xiaofei Li; Xin Liu (BMC Public Health)
Abstract Objective This study aimed to examine the factors that affect treatment delay in early childhood caries (ECC), guided by a modern medical model. This study attempted to analyze the pathways influenced by these factors and provide a theoretical foundation for designing targeted intervention programs. Methods Data were collected from young children who visited the department of stomatology at a tertiary hospital from January to December 2023. Data were collected via a general information survey questionnaire, the Scale of Oral Health Outcomes for 5-year-old Children (SOHO-5), the Children’s Fear Survey Schedule-Dental Subscale-Chinese (CFSS-DS-C), the Parental Caregiver Perceptions Questionnaire-8 (P-CPQ-8), the Family Impact Scale (FIS-8), and the Perceived Barriers to Health Care-Seeking Decision-Chinese (PBHSD-C). The data in this study were analyzed using a variety of statistical tests, including the Kruskal-Wallis and Mann-Whitney tests, correlation analysis, multiple stepwise regression analysis, and structural equation modeling (SEM). Results The treatment delay score of early childhood caries was 36.77 ± 10.11, indicating that the state of early childhood caries was currently at a moderate level of delay. The SOHO-5 score was 6.41 ± 1.78, the CFSS-DS-C score was 23.60 ± 6.91, the P-CPQ-8 score was 18.43 ± 4.33, and the FIS-8 score was 18.66 ± 4.28. Multi-factor analysis revealed key factors affecting treatment delay, including permanent residence, medical insurance type, oral health habits, reasons for visit, first symptoms, the time of first discovery of oral problems, brushing teeth before bedtime every day, a genetic history of dental caries and the staging of dental caries. A positive correlation existed between oral health, children’s dental fear and treatment delay, whereas social support was negatively correlated with treatment delay. The SEM, which is based on the modern medical model, revealed that children’s dental fear plays a mediating role in the relationships among social support, oral health, and treatment delay. Conclusion The present study developed a novel model to study the ECC treatment delay, elucidated the causal links between the identified variables, and proposed potential intervention strategies to enhance oral health awareness, knowledge, and skills among young children and their parents. These strategies can help improve children’s dental visiting behavior and reduce treatment delay.